Abuse Of Authority By Police Commander In Djoko Tjandra Case - Ismi Tri Septiyani; Rida Nabila; Muhammad Rifqi; Citra Oki Wijaya Kusuma (Syiar Hukum, 2022)
In one of the Indonesian law enforcement agencies, where the three army generals Indonesia polices, Brigadier General Prasetijo Utomo, Inspector General Napoleon Bonaparte, and Brigadier General Slamet Nugraha Wiwoho have committed a gross abuse of power. The three of them helped djoko tjandra commit the corruption of the Bali bank and other crimes in trying to escape the legal process, such as helping him get a covid release letter and helping him escape the country. Djoko Tjandra bribed law enforcement officials, along with the three generals, and Djoko Tjandra's bribes to the prosecutor on the case of prosecutor Pinangki. What an irony in a nation of law. Its law enforcement taints the name, as did the three former high-ranking police officers. Perhaps not only those who took bribes from Djoko Tjandra but with the arrest of law enforcement opened the eyes of Indonesians that there was nothing to believe in, that law enforcement was lax in its duty.